2019
DOI: 10.1371/journal.pone.0221970
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between volume status and possibility of pulmonary hypertension in dialysis naive CKD5 patients

Abstract: Background Chronic fluid overload is common in patients with chronic kidney disease (CKD) and can with time lead to poor prognosis regarding to the cardiovascular events. Serum NT-proBNP and OH/ECW might reflect fluid status of the patients, and the maximal tricuspid regurgitation velocity (TRVmax) could reflect systolic pulmonary artery pressure (SPAP). We investigated the relationship between markers of volume status and marker of pulmonary hypertension (PH) in non-dialysis CKD5 (CKD5-ND) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Previous studies have reported a relationship between PH and renal dysfunction (4,13). Renal dysfunction is thought to contribute to the development of PH (2).…”
Section: Associations Between Pasp and Electrolytes Parameters Cr Anmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have reported a relationship between PH and renal dysfunction (4,13). Renal dysfunction is thought to contribute to the development of PH (2).…”
Section: Associations Between Pasp and Electrolytes Parameters Cr Anmentioning
confidence: 94%
“…Pulmonary hypertension (PH) is reported to be one of the most frequent complications among various diseases including endstage renal disease (ESRD) and is characterized by progressively increased pulmonary arterial pressure (PAP) (1)(2)(3)(4). PH is the leading cause of right heart failure among cardiovascular diseases (1,5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [13,14] showed right atrial dilation, increase in pulmonary artery pressure and lowering of longitudinal right ventricular function in haemodialysis patients in comparison with healthy population. The presence of right ventricular (RV) systolic dysfunction [15] and also of pulmonary hypertension [16] were associated with higher all-cause mortality in haemodialysis patients and are strongly influenced by volume overload [17].…”
Section: Introductionmentioning
confidence: 99%
“…A recent bioimpedance‐based study has demonstrated that hemodialysis patients with PAH had a greater degree of overhydration (OH) [13]. Similarly, BIA indicating the volume status, including OH and OH/extracellular water (ECW) [14], differed considerably between stage 5 chronic kidney disease (CKD) dialysis‐naive patients with PAH and those without it [15].…”
Section: Introductionmentioning
confidence: 99%